2016
DOI: 10.18632/oncotarget.6874
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monitoring of EGFR mutations in plasma predicts outcomes of NSCLC patients treated with EGFR TKIs: Korean Lung Cancer Consortium (KLCC-12-02)

Abstract: We hypothesized that plasma-based EGFR mutation analysis for NSCLC may be feasible for monitoring treatment response to EGFR TKIs and also predict drug resistance. Clinically relevant mutations including exon 19 deletion (ex19del), L858R and T790M were analyzed using droplet digital PCR (ddPCR) in longitudinally collected plasma samples (n = 367) from 81 NSCLC patients treated with EGFR TKI. Of a total 58 baseline cell-free DNA (cfDNA) samples available for ddPCR analysis, 43 (74.1%) had the same mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
121
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 41 publications
17
121
0
2
Order By: Relevance
“…Because ctDNA clearance appears important for clinical evaluation, MAF is also appropriate to analyze ctDNA dynamics under treatment. Our results are consistent with previous findings showing that ctDNA normalization before the third cycle of treatment in EGFR -mutated patients is associated with improved OS [36,37]. …”
Section: Discussionsupporting
confidence: 93%
“…Because ctDNA clearance appears important for clinical evaluation, MAF is also appropriate to analyze ctDNA dynamics under treatment. Our results are consistent with previous findings showing that ctDNA normalization before the third cycle of treatment in EGFR -mutated patients is associated with improved OS [36,37]. …”
Section: Discussionsupporting
confidence: 93%
“…Zhu et al [19] found that the plasma EGFR mutation testing sensitivity of ddPCR was greater than 80%, and the specificity was approximately 95.8-98.4%, compared with ARMS testing of matched tumor tissues. In our study, the specificity for plasma EGFR testing by ddPCR was 96.7-98.8%, similar to the results reported by Zhu et al However, the sensitivity in our study was lower than those previously reported for the ddPCR method [19, 20, 24] and the Cobas 4800 blood test [25], but higher than those reported for ARMS [12, 26] or other tests [27]. More than 200 NSCLC patients were enrolled in our study, and the blind method was adopted, so our study was closer to a clinical practice situation.…”
Section: Discussionsupporting
confidence: 91%
“…A prospective analysis of advanced NSCLC patients demonstrated that patients with complete resolution of ctDNA at either 2 or 6 weeks after treatment, exhibited a lower treatment discontinuation rate (0% at initial and 4% at second reimaging) compared to patients without complete resolution (33% at initial and 56% at second reimaging), presumably correlating with radiographic response and emergence of acquired resistance (11). Another prospective study followed 62 EGFR mutant NSCLC patients receiving TKI therapy with serial plasma ctDNA testing (56 (57). All 40 patients with EGFR mutations at baseline showed a significant reduction of mutant copies (>50%) in plasma during the first 2 months after treatment.…”
Section: Role In Longitudinal Clinical Monitoringmentioning
confidence: 99%